ITINERARIO ESCULTÓRICO OCHOCENTISTA. PASEO POR EL AMOR, LA VIDA, LA MUERTE: LA REALIDAD O ILUSIÓN. (HOMENAJE AL JOVEN DE CNIDO) - Nicolás Gómez, Dora (Imafronte, 1997)
This article presents a,first reflection on the progressive abandoning of the natural model as the reference-point, for western sculpture. The human being. and all living-beings in general, are no longer the only object and subject of sculpture. The naturalist, or humanist approach, has its last flowering in 18th century sculpture. but it is also the almost definitive expression of a farewell to the fidelity to the natural model.